Provider advice on physical activity and nutrition in twin pregnancies: a cross-sectional electronic survey - Kara M. Whitaker; Meghan Baruth; Rebecca A. Schlaff; Hailee Talbot; Christopher P. Connolly; Jihong Liu; Sara Wilcox (BMC, 2019)
Abstract Background Health care providers should counsel pregnant patients on physical activity and nutrition to improve pregnancy outcomes. However, little is known about provider advice on these lifestyle behaviors among women pregnant with twins, a growing population at high risk for pregnancy complications. We examined the prevalence and content of provider advice on physical activity and nutrition among women pregnant with twins. Methods A cross-sectional electronic survey was administered to 276 women who delivered twins in the past 3 years and received prenatal care in the United States. The proportion of women reporting provider advice on physical activity and nutrition during prenatal visits (yes/no) was assessed and open-ended questions examined the content of provider advice. Bivariate differences in participant characteristics, stratified by provider advice on physical activity and nutrition (yes/no), were assessed. Responses from open-ended questions were examined using a content analysis approach to identify commonly reported advice on physical activity and nutrition. Results Approximately 75 and 63% of women reported provider advice on physical activity and nutrition, respectively, during their twin pregnancy. Women who recalled advice on physical activity most commonly reported recommendations to walk at a light to moderate intensity level. However, few women reported physical activity recommendations consistent with current guidelines, and approximately 55% of women reported provider advice to limit or restrict activity during their pregnancy, including bedrest. Nutrition advice was focused on eating a healthy, balanced diet and increasing protein intake. More women reported self-initiating the conversation on physical activity with their provider (40%) compared to nutrition (21%). Despite limited advice, 70% of women reported being satisfied or very satisfied with the information they received from their provider on physical activity or nutrition. Conclusions The majority of women reported provider advice on physical activity and nutrition during their twin pregnancies. However, advice was limited in detail, and physical activity levels were commonly restricted, despite the lack of evidence that activity restriction is beneficial during pregnancy. More research is needed to determine the optimal physical activity and dietary patterns in twin pregnancies to facilitate clear and consistent provider counseling on these lifestyle behaviors.